2019
DOI: 10.1007/s11606-019-05470-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between Opioid Prescribing in Medicare and Pharmaceutical Company Gifts by Physician Specialty

Abstract: BACKGROUND: The association between pharmaceutical industry promotion and physician opioid prescribing is poorly understood. Whether the influence of industry gifts on prescribing varies by specialty is unknown. OBJECTIVE: To examine the relationship between opioidrelated gifts to physicians and opioid prescribing in the subsequent year across 7 physician specialties. DESIGN: Panel study using data from 2014 to 2016. PARTICIPANTS: 236,103 unique Medicare Part D physicians (389,622 physician-years) who received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…During this time, physicians wrote more than seventy opioid prescriptions per year for every hundred Americans (CDC 2019b). Unsurprisingly, studies have found the receipt of payments from opioid companies is associated with increases in physicians' prescribing rates (Hadland et al 2018;Hollander et al 2019). That is, of course, the reason drug companies engage in such practices, and similar effects have been found in relation to a variety of other prescription drugs.…”
Section: Influencing Physicians and Health Professionalsmentioning
confidence: 93%
See 1 more Smart Citation
“…During this time, physicians wrote more than seventy opioid prescriptions per year for every hundred Americans (CDC 2019b). Unsurprisingly, studies have found the receipt of payments from opioid companies is associated with increases in physicians' prescribing rates (Hadland et al 2018;Hollander et al 2019). That is, of course, the reason drug companies engage in such practices, and similar effects have been found in relation to a variety of other prescription drugs.…”
Section: Influencing Physicians and Health Professionalsmentioning
confidence: 93%
“…Between 2014 and 2015, roughly one in seven physicians in the United States received opioid-related gifts from pharmaceutical companies (Hollander et al 2019); another analysis of a similar period puts the figure for family physicians even higher at one in five (Hadland, Krieger, and Marshall 2017). During this time, physicians wrote more than seventy opioid prescriptions per year for every hundred Americans (CDC 2019b).…”
Section: Influencing Physicians and Health Professionalsmentioning
confidence: 99%
“…Branded PGA use for each prescriber was calculated as a percentage of total days supplied of PGA eye drops. Previous works comparing Open Payments data and individual-level prescribing patterns identified prescriber sex, 3,5,13,34-37 specialty, [2][3][4][5][6][7][8][34][35][36][37][38][39][40][41][42] total prescribing volume, 5,34,35,39,41 US Census region, 34,35 and zip code-based urban vs rural designation 5 as potentially significant covariates. Our analysis showed collinearity between US Census region and USPS Rural Urban Commuting Area urban vs rural designation, with Rural Urban Commuting Area being a stronger predictor of both branded PGA use and reported TOV from PGA makers.…”
Section: Key Pointsmentioning
confidence: 99%
“…Four of these had medical oncologist participants (27,(38)(39)(40), and five had both haematologists and oncologists. (26,(41)(42)(43)(44) All were based in the US, and eight used the Open Payments database as an exposure against Medicare prescribing data as a dependent variable.…”
Section: Category 2: Investigations Of Financial Ties Among Influenti...mentioning
confidence: 99%